Causes of short stature in Iraqi hospital based study patients - AlZubaidi, Munib A.; Saleh, Maher M.; Jawad, Zahraa M. (Journal of the Faculty of Medicine Baghdad, 2017)
Backgrounds: Growth is an important objective parameter of general health of the child. Normal growth requires adequate nutrition along with various hormonal stimuli. Short stature is a common cause of referral to pediatric endocrinologists.Objectives: To find the causes of short stature in patients referred to pediatric endocrinology clinic of children welfare teaching hospital, the significance of bone age assessment and the variation of growth hormone level in these patients.Patients and methods: This prospective study was carried out in the endocrine clinic of Children Welfare Teaching Hospital/Medical City over ten months period, included 150 patients. A proper detailed medical history was taken, physical examination performed included growth parameters, and general investigations with bone age, thyroid function test, celiac screening and growth hormone level were done for all patients. Growth hormone stimulation test was done when indicated and phenotype, Karyotyping was done in selected cases.Result: The total number of patients included in this study was150, ranging from ≥ 2 to 16 years old, and the male to female ratio was 1.14:1. The relationship between age and gender is significant(p-value 0.04).The commonest etiology was endocrine causes in 92(61.33%), non-endocrine causes in 34(22.67%) and normal variant in 24(16%) patients. Bone age was delayed in 86(57.33%) and normal in 6(4%) of endocrine cause which is highly significant (p-value< 0.001), and in non-endocrine causes it was delayed in 24(16%) and not delayed in 10(6.67%) patients which is significant (p-value